2018
DOI: 10.1021/jacs.8b08316
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Homochirality and Hydrothermal Stability in Zn4O-Based Porous Crystals

Abstract: The [Zn4O]6+ cluster is well-known to form the archetypal MOF-5 topology with dicarboxylate ligands. Here we report two new materials (CPM-300 and -301) that show dramatic alteration of topological and chemical behaviors of [Zn4O]6+ clusters. In CPM-300, [Zn4O]6+ untypically forms the MIL-88/MOF-235 type framework with a small pentane-ring-based chiral dicarboxylate. In contrast, in CPM-301, when mediated by [Zn9(btz)12]6+ clusters (btz = benzotriazolate), the MOF-5 topology is regenerated with the same chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The two POMCFs are relatively stable, mainly due to the high-temperature hydrothermal synthesis and small pore sizes. There are many other strategies that can be used for the synthesis of stable Zn-MOF such as the introduction of hydrophobic methyl groups [ 49 ]. NNU-13 can adsorb CO 2 with the maximum uptake of 34.1 cm 3 /g at 298 K, while NNU-14 can adsorb CO 2 with the maximum uptake of 14.3 cm 3 /g at 298 K (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two POMCFs are relatively stable, mainly due to the high-temperature hydrothermal synthesis and small pore sizes. There are many other strategies that can be used for the synthesis of stable Zn-MOF such as the introduction of hydrophobic methyl groups [ 49 ]. NNU-13 can adsorb CO 2 with the maximum uptake of 34.1 cm 3 /g at 298 K, while NNU-14 can adsorb CO 2 with the maximum uptake of 14.3 cm 3 /g at 298 K (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that surface hydrophobicity would increase the water stability of MOFs. 26,31,[33][34][35][36][37] In order to examine the water stability of HKUST-1-P, both parent and modified MOF samples were exposed to water for 3 days. HKUST-1 can easily settle down to the bottom of the water owing to its good hydrophilicity (Figure 2c).…”
Section: Page 5 Of 22 Ccs Chemistrymentioning
confidence: 99%
“…However, neither gas nor water vapor adsorption study was performed to confirm their permanent porosity and hydrophobicity. Recently, Zhao et al reported two hydrophobic MOFs, [Zn 4 O(RR‐cam) 3 ] (CPM‐300) and [Zn 4 O(RRcam) 3 ][Zn 9 (btz) 12 (RR‐cam) 3 ] (CPM‐301), synthesized from a pentane‐ring‐based chiral dicarboxylic acid, RR‐H 2 cam . CPM‐300 was a 6‐connected framework with the acs topology constructed by 6‐connected [Zn 4 O] 6+ clusters and RR‐cam 2− ligands, and CPM‐301 was a binodal 6‐connected framework with the pcu topology constructed by 6‐connected [Zn 4 O] 6+ and 6‐connected [Zn 9 (btz) 12 ] 6+ (with btz − serving as terminal ligands) clusters bridged by RR‐cam 2− ligands ( Figure ).…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%
“…f) The connection between the [Zn 4 O] 6+ and [Zn 9 (btz) 12 ] 6+ clusters. Adapted with permission . Copyright 2018, American Chemical Society.…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%